Eksplorasi Perubahan Fisik dan Gejolak Emosional pada Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis: Pendekatan Kualitatif - Lilin Rosyanti; Indriono Hadi; Kusman Ibrahim (Health Information : Jurnal Penelitian, 2018)
Patients with terminal kidney failure report limitations and physical changes, psychological functions, and weaknesses that have a negative effect on health status and a decrease in survival. Progress in dialysis technology and disease management still raises many complaints both physically and psychologically by increasing the mortality rate of patients undergoing hemodialysis. In 2008, there were about 1.75 million patients worldwide who regularly received kidney replacement therapy in the form of dialysis, about 1.55 (89%) million underwent hemodialysis (HD) and around 197.000 (11%) used peritoneal dialysis (PD). This research explored the experience of hemodialysis patients with physical changes and emotional turmoil. This was a descriptive qualitative research that aimed to reveal broadly and deeply the causes and things that influenced the pattern of life behavior of patients from aspects of sexuality. The study found two categories of themes (1) physical changes and physical complaints: black facial skin, damaged teeth,body thin, body weak, and fatigue. (2) feeling and emotional turmoil: not accepting and fearing death, feeling helpless and useless, apologizing and suggesting that the couple remarry. The exploration experience of physical changes and emotional turmoil of hemodialysis patients were influenced by physical, physiological, psychological, social and spiritual aspects as well as values, cultures that exist in the lives of participants.